Critical Factors Affecting Team Work Efficiency in BIM-Based Collaborative Design: An Empirical Study in China - Wang, Jiayuan; Yuan, Zikui; He, Zhilin; Zhou, Fuping; Wu, Zezhou (Buildings (Basel), 2021)
Building information modeling (BIM) can theoretically facilitate collaboration among diverse design participants in construction projects, but in practice, its implementation tends to prolong the design period. Existing literature has examined some technical and managerial causes of this problem but still lacks an overall coverage of related factors. This study aims to identify the comprehensive factors affecting the teamwork efficiency in China’s BIM-based collaborative design, and to investigate the critical factors and their interactions. Based on the input-process-output theory, this study initially established a hypothetical model. Potential factors were further identified through the literature review and semi-structured interviews. Questionnaire survey was conducted, and structural equation modeling was used for analysis. The results indicated that the team cooperation atmosphere is the most significant factor, followed by the collaborators’ learning ability, comfort of the working environment, BIM software function, and the characteristics and arrangement of the design task (CADT). Besides, the CADT negatively affects the teamwork efficiency through the human interaction process, while other factors exert positive impacts by affecting both the personal work process and the human interaction process. The findings can help design units to determine the management focus of BIM-based collaborative design and prioritize the allocation of limited resources accordingly to maximize teamwork efficiency.